Talon Cusp Type I: Restorative Management - Rafael Alberto dos Santos Maia; Wanessa Christine de Souza-Zaroni; Raul Sampaio Mei; Fernando Lamers (Case Reports in Dentistry)
The teeth are formed during intrauterine life (i.e., gestation) during the odontogenesis stage. During this period, the teeth move until they enter the oral cavity. This course covers various stages of dental development, namely, initiation, proliferation, histodifferentiation, morphodifferentiation, and apposition. The talon cusp is an anomaly that occurs during morphodifferentiation, and this anomaly may have numerous adverse clinical effects on oral health. The objective of this study was to report a case of “Talon Cusp Type I” and to discuss diagnostic methods, treatment options for this anomaly, and the importance of knowledge of this morphological change among dental professionals so that it is not confused with other morphological changes; such knowledge is required to avoid unnecessary surgical procedures, to perform treatments that prevent caries and malocclusions as well as enhancing aesthetics, and to improve the oral health and quality of life of the patient.